MBKM POLICY AND PRACTICE AT UNIVERSITAS SILIWANGI: AN ANALYSIS OF ALIGNMENT, EFFECTIVENESS, AND IMPACT ON STUDENT COMPETENCIES - Ceceng Saepulmilah; Luqman Al – Hakim Musthafa; Ika Purnama Alam; Diansyah Permana; Supiana Supiana; Qiqi Yuliati Zaqiah (Jurnal Konseling Pendidikan Islam, 2026)
The transformation of higher education in Indonesia through the Merdeka Belajar–Kampus Merdeka (MBKM) policy requires universities to strengthen curriculum flexibility, experiential learning, and institutional readiness. However, the alignment between policy design and real implementation varies across institutions, particularly in regional universities. This study aims to analyze the consistency between MBKM policy documents and implementation practices at Universitas Siliwangi, evaluate the effectiveness of its programs in enhancing student competencies, and identify the structural and operational challenges influencing program outcomes. Using a qualitative case study approach, data were collected through in-depth interviews with supervising lecturers, MBKM coordinators, and student participants, supported by institutional documents such as curricula, guidelines, decrees, and activity reports. The findings show that Universitas Siliwangi has established policy frameworks aligned with national MBKM principles, reflected in curriculum integration, recognition of off-campus learning, and structured administrative support for programs such as MSIB, PMM, Teaching Campus, and community-based projects. Students participating in MBKM reported significant improvements in communication, independence, problem-solving, and workplace readiness. However, several challenges persist, including uneven curriculum harmonization, limited partner availability in certain study programs, varying levels of student readiness, and the need for a more adaptive academic information system. Overall, the study concludes that MBKM implementation at Universitas Siliwangi is progressing well, yet requires strengthened governance, improved cross-unit coordination, and expanded partnerships to achieve optimal and sustainable transformation in higher education.